Mammary gland morphology and gene expression signature of weanling male and female rats following exposure to exogenous estradiol. (September 2013) - Miousse, Isabelle R; Gomez-Acevedo, Horacio; Sharma, Neha; Vantrease, Jamie; Hennings, Leah; Shankar, Kartik; Cleves, Mario A; Badger, Thomas M; Ronis, Martin JJ
In order to characterize the actions of xenoestrogens, it is essential to possess a solid portrait of the physiological effects of exogenous estradiol. We assessed effects of three doses of exogenous estradiol (E2) (0.1, 1.0 and 10 µg/kg/day) given between postnatal days 21 and 33 on the mammary gland morphology and gene expression profiles of male and female rats compared to vehicle-treated controls. The male mammary gland was more responsive to E2 treatment than in females, with 509 genes regulated >2-fold in a dose-dependent manner in males and only 174 in females. In males, E2 treatment significantly ( P < 0.01) increased the number of terminal end buds (TEBs) and the expression of proliferating cell nuclear antigen (PCNA) protein ( P < 0.05), both of which are indicators of proliferation. This change was linked to a significant increase ( P < 0.05) in the expression of the gene encoding amphiregulin, which is known to induce TEB formation. There was also a dose-dependent increase ( P < 0.001) in the estrogen-regulated gene encoding the progesterone receptor. In intact females, despite lack of changes in mammary morphology, we observed a dose-dependent increase ( P < 0.05) in the expression of genes encoding three milk proteins: whey acidic protein, casein beta and casein kappa. There was a significant ( P < 0.05) downregulation of both estrogen receptors in response to E2 treatment. These results suggest that mammary glands of male rats are very sensitive to exogenous E2 during development post-weaning. The dose-dependent increase observed in amphiregulin and progesterone receptor gene expression was linked to morphological changes and represents a reliable and sensitive tool to evaluate estrogenicity. In contrast, intact weanling female rats were less responsive.